2015
DOI: 10.1302/0301-620x.97b10.34927
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lumbar instrumented circumferential fusion on the development of adjacent vertebral compression fracture

Abstract: We evaluated the impact of lumbar instrumented circumferential fusion on the development of adjacent level vertebral compression fractures (VCFs). Instrumented posterior lumbar interbody fusion (PLIF) has become a popular procedure for degenerative lumbar spine disease. The immediate rigidity produced by PLIF may cause more stress and lead to greater risk of adjacent VCFs. However, few studies have investigated the relationship between PLIF and the development of subsequent adjacent level VCFs. Between January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…A recent systematic review examining the role of IBF in the setting of DLS found that the majority of available studies identified no radiographic or clinical outcome difference between IBF and other surgical treatments [22]. The increased rigidity conferred by the addition of an interbody device may contribute to elevated rates of adjacent segment degeneration (ASD) and compression fracture [23][24][25][26]. However, conflicting data indicate that IBF may instead protect against ASD by generating more segmental lordosis [27].…”
Section: Indications For Interbody Fusionmentioning
confidence: 99%
“…A recent systematic review examining the role of IBF in the setting of DLS found that the majority of available studies identified no radiographic or clinical outcome difference between IBF and other surgical treatments [22]. The increased rigidity conferred by the addition of an interbody device may contribute to elevated rates of adjacent segment degeneration (ASD) and compression fracture [23][24][25][26]. However, conflicting data indicate that IBF may instead protect against ASD by generating more segmental lordosis [27].…”
Section: Indications For Interbody Fusionmentioning
confidence: 99%
“…The prevention of motion of the surgical segment leads to high stress on the fixation implant, increasing mobility, and intradiscal pressure at adjacent levels 3 . This may result in adjacent segment degeneration and loosening/rupture of the fixation implant [4][5][6][7][8][9] . Non-fusion and dynamic fusion instruments have been designed to prevent adjacent segment disease.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Li et al found that rigid fusion after posterior lumbar interbody fusion increases stress and leads to a greater risk of adjacent VCFs in osteoporotic patients. 31 Pooled data demonstrated a significant difference in the incidence of subsequent VCFs (RD=−0.24, P <0.001): 7.1% in patients receiving a bisphosphonate and 30.6% in controls. Thus, bisphosphonates prevent subsequent VCFs in patients with lumbar fusion.…”
Section: Discussionmentioning
confidence: 89%